KONVERSI PAKAN RATA-RATA PADA BABI PERIODE STARTER UMUR 30-36 HARI DI CV ADHI FARM - , DWI ANITA FEBRIANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Non-ruminant animal health management training in pigs have been done in CV Adhi Farm. The aims of the management training were found learn about the management of feed particularly on FCR (Feed Conversion Ratio). Job Training was conducted on April 22-27, 2013, which began at 07.30 am until 16.00 pm to follow the activities, such as feeding pigs from starter to finisher phase, mixing and feed milling, cleaning cages, castration, treatment, artificial insemination (IB), and help the process of parturition. Besides, it also had a discussion with the owner and worker in the farm. The conclusion of the observation that the feed conversion ratio for weaning pigs aged 30-36 days obtained 1,71. It is means that 1 kg of body weight could be increased by consume 1,71 kg of feed.